Woodwork Technology And Vocational Skills: A Pragmatic Approach To Youth Unemployment In Nigeria - Bamidele kareem Wahab; Omuya, Abubakar Halima; Ogbanje, Okwori Robert; Mik, Muhammed Bala (International Journal of Advanced Humanities Research)
Unemployment is a clear global problem that leaves no nation untouched both developing and developed nation of the world. This scenario is seriously agitating for national attention particularly Nigeria during this economic crisis. This paper has delved into exploitation of woodwork skills and vocational education as an approach towards reducing unemployment in Nigeria. The objectives were to seek factors responsible for youth employment and possible approach to eradicate the problem. Three research questions were formulated to guide the study while two null hypotheses were tested at 0.05level of significant. A descriptive survey design was used for the study while a set of 45 items questionnaire was the instrument used to obtain data from the two categories of respondents. Four hundred and eighty-five youth and adult from North Central zone were used as population for the study. Standard Deviation were used to analyse data obtained. The study findings includes: Government should give attention to unemployment in Nigeria because the respondents agreed that factors such as lack of woodwork and vocational skills needed by youth in the society among others are responsible for youth unemployment  in Nigeria. Based on these findings, it was recommended that parents, NGO, industries and Government at all level that is Federal, State and Local government and Nigeria Society should give adequate recognition to woodwork technology and vocational skills by providing adequate funding to obtain necessary tools, equipment and infrastructure for technical colleges and tertiary institution offering the programme.